Tales of justice and rituals of divine embodiment: oral narratives from the central Himalayas - Malik, Aditya (Oxford University Press, 2016)
Thinking about justice and being human -- God of justice -- Ideas of justice -- Writing intimacy -- Possession, alterity, modernity -- Transformations -- Dancers